Container Loading And Unloading Process At Container Freight Station (CFS) At PT. Prima Indonesia Logistik Belawan - M. Heru Dwiyanto; Suparman Suparman; Eka Fransiska (Ocean Engineering : Jurnal Ilmu Teknik dan Teknologi Maritim, 2024)
The purpose of this study is to determine how the Container loading and unloading process at the Container Freight Station (CFS) at PT. Prima Indonesia Logistik Belawan. The methodology used in making the research is a field study where the author conducts observations in the field (observations) and interviews directly with the company and a library study where the author obtains research material or materials from books in the library or other reading sources related to the discussion in the author's research. The results obtained in this study are the Container loading and unloading process at the Container Freight Station (CFS) at PT. Prima Indonesia Logistik Belawan has not run optimally due to obstacles that occur during loading and unloading such as frequent machine damage to the operator's equipment, negligence of the Tally Man officers causing delays in the container loading and unloading process, the occurrence of escape in surveying containers, and a long cleaning process.